Fractionation of Buckwheat Seed Phenolics and Analysis of Their Antioxidant Activity - Karamać Magdalena; Biskup Izabela; Kulczyk Anna (Polish Journal of Food and Nutrition Sciences)
Five fractions of phenolic compounds were obtained from the extract of common buckwheat seed (Fagopyrum esculentum Moench) using Sephadex LH-20 column chromatography with methanol as a mobile phase. The total phenolics content ranged from 19.8±1.5 (fraction I) to 164±2.2 mg (+)-catechin eq/g (fraction IV). The profiles of phenolic acids and flavonoids in the fractions were analysed using RP-HPLC-DAD. The antioxidant activity was tested as ABTS⋅+ and DPPH⋅ scavenging activity and capability to reduce the Fe(III)/2,4,6-Tris(2-pyridyl)-s-triazine complex to the ferrous form. Results were expressed as Trolox equivalent antioxidant capacity (TEAC), IC50 and ferric reducing antioxidant power (FRAP) values, respectively. The highest antioxidant activity was noted for fraction IV that was predominated by flavones. TEAC, IC50 and FRAP values were: 1.47±0.01 mmol Trolox eq/g, 0.058±0.003 mg/assay and 2.18±0.05 mmol Fe(II)/g, respectively. Rutin constituted 77.7% of the compounds identified in fraction III. The antiradical activity and reducing capability of this fraction were lower compared to fraction IV, but significantly higher than in fractions I and II. The main phenolic compounds of fractions I and II were phenolic acids (caffeic, 5-O-caffeoylquinic and p-coumaric). The antioxidant activity of fraction V was similar to that of fraction III.